Are clonal plants more frequent in cold environments than elsewhere? - Klimešová, J. (Jitka); Doležal, J. (Jiří) (Plant Ecology & Diversity, 2011)
In stressful environments, clonality provides plants with reproductive insurance and conservation of limiting nutrients. Hence, clonal growth is expected to be more frequent in floras of cold environments, such as the alpine and arctic regions, than in temperate regions. Evidence for this is largely based on comparisons of the ratio of clonal to non-clonal vascular plant species in local floras, as it is difficult to obtain reliable data that assess the extent of clonality in plant communities. Here we review, to the best of our knowledge, the most comprehensive dataset on the proportion of clonal vascular plant species in regional floras of cold environments/regions. Contrary to our expectations, the results do not show a higher proportion of clonal species in cold environments than in the reference regions. The results rather show regional differences explicable by different species pools and/or climates.